Nutraceutical potential of moroccan Juglans regia: phytochemical profiling and multi-modal evaluation of bioactivities - Drioiche, Aziz; Al kamaly, Omkulthom; Baammi, Soukayna; Zibouh, Khalid; Amaiach, Rachid; Bennani, Laila; Abdelhakim, El Ouali Lalami; El Imache, Ahde; EL Makhoukhi, Fadoua; Sahpaz, Sevser; Zair, Touriya (Frontiers in Chemistry, 2025)
This study explores the therapeutic potential of J. regia from Morocco through an in-depth phytochemical analysis and biological evaluations using in vitro, in vivo, and in silico approaches. The extracts of J. regia were obtained through decoction and Soxhlet extraction, utilizing water and a water-ethanol mixture as extraction solvents. Phenolic compounds, flavonoids, condensed tannins, and hydrolyzable tannins were quantified using spectrophotometric methods. Chromatographic analysis by HPLC/MS enabled the identification and characterization of the main bioactive compounds. Biological activities were assessed through antioxidant (DPPH, FRAP, TAC), antimicrobial (MIC, MBC), anticoagulant (prothrombin time and activated partial thromboplastin time), and antidiabetic (inhibition of α-amylase and α-glucosidase enzymes, in vivo tests) assays. In silico simulations were conducted to study the molecular interactions between the significant compounds and their biological targets. The extracts, obtained by decoction and Soxhlet extraction, revealed a richness in bioactive compounds, notably pedunculagin (45.12%), hydrojuglone glucoside (14.51%), and gallic acid (5.18%), with high concentrations of polyphenols (42.105 mg GAE/g) and flavonoids (14.888 mg QE/g). Antioxidant assays, including TAC, FRAP, and DPPH, revealed significant antioxidant activity. Additionally, the aqueous extract exhibited notable antimicrobial efficacy, demonstrating minimum inhibitory concentrations (MICs) of 150 μg/mL against Acinetobacter baumannii and Shigella sp., and 2,500 μg/mL against Aspergillus niger and particular Candida species. The anticoagulant activity was evidenced by prolonged prothrombin time (98.9 s) and activated partial thromboplastin time (134.2 s at 11.5 mg/mL), and the antidiabetic activity was confirmed by the inhibition of α-amylase (EC50 = 104.8 μg/mL) and α-glucosidase (EC50 = 12.12 μg/mL) enzymes, as well as by a reduction in postprandial hyperglycemia in treated rats (400 mg/kg). In silico simulations revealed a strong affinity of pedunculagin for key biological targets, supporting its therapeutic potential. In conclusion, Juglans regia emerges as a promising natural resource for applications in the pharmaceutical, nutraceutical, and cosmetic fields, although clinical studies are required to validate its efficacy and safety.